Global Investment Promotion Best Practices 2012 - World Bank Group (Washington, DC, 2014)
Global flows of foreign direct investment (FDI) declined severely during the recent economic and financial crisis. As the crisis eased, recovery in world economies spurred a resurgence of FDI, and that in turn reignited competition for investments among host countries. Especially in emerging markets, governments long have prized FDI as a source of much-needed capital and jobs. But in the 21st century, governments value FDI as much or more as a source of technology and know-how. Policymakers have witnessed how knowledge brought by foreign investors can spill over to local firms, bolster skills in the local workforce, and thus increase the overall competitiveness of their economies. To foster development of intellectual capital as well as businesses and jobs, governments increasingly recognize the importance of cultivating FDI. Providing business and investment climate information is a crucial component of IPI activities in all economies. But IPIs can gain particular advantage in those settings where investors find it most difficult to obtain reliable information and meet bureaucratic requirements. Research shows, for example, that investment promotion is more effective in economies where English is not an official language, and in economies that are more culturally distant from the investors corporate homes. Investment promotion also has more impact in countries with less effective governments and in economies that erect more barriers to launching a business (such as more time to obtain a construction permit). In this 2012 edition, GIPB focuses specifically on information provision in two sectors, tourism and agribusiness. This focus should be of particular use to economies that seek or are considering seeking FDI in those sectors.